BEHAVIORAL INTENTION KONSUMEN TERHADAP HAK CIPTA KASET DI INDONESIA - Nidjat Ibrahim; Anggraeny Novitasari (Universitas Trisakti, 2004)
For some years there are always happen the bribery of cassette industry which make loss for the musicindustry in Indonesia. This is the importantreason why we need the research to explore the problem that need. The objective of this paper is to discuss about consumer behavioral intention for the cassette property right in Indonesia and the factors which infiuence it. The faclors which used is attilude, subjective nom, and aiso behavioral control. For the data exploration we used the structural equation model and also uşed the software Amos 4.0. Reliability test and validity test was done for the questioner which used all the variable above. Byempiric we can find that attitude variable, subjective norm, and behavicral control has been influenced positively for consumer behavioral intention in the cassette property right in Indo- nesia with = 5%. The implication is the Indonesian govemment should implement precisely in the implementation of Indonesian Property Right Act because severat of Indonesian peopte, especially some buyers still concem with the protection of property right in one product.